2019
DOI: 10.3390/nu11122971
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and NAFLD: What We Know and Questions That Still Need to Be Answered

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the hepatic manifestation of metabolic syndrome and is expected to become the leading cause of end-stage liver disease worldwide over the next few decades. In fact, NAFLD encompasses different clinical scenarios, from the simple accumulation of fat (steatosis) to steatohepatitis (NASH), NASH-cirrhosis, and cirrhosis complications. In this context, it is fundamental to pursue strategies aimed at both preventing the disease and reducing the progression of liver fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 105 publications
3
73
0
4
Order By: Relevance
“…Thus, there may have been a lack of contrast in dietary habits, and we may not have been able to detect weaker associations. At the same time, the present findings are consistent with previous findings from other study types and populations [12,13], and the fact that diet quality was inversely associated with NAFLD in this particular group of individuals does point to meaningful effects of diet on liver fat beyond energy balance. As stated above, however, larger iso-caloric interventions are needed to confirm the present observations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, there may have been a lack of contrast in dietary habits, and we may not have been able to detect weaker associations. At the same time, the present findings are consistent with previous findings from other study types and populations [12,13], and the fact that diet quality was inversely associated with NAFLD in this particular group of individuals does point to meaningful effects of diet on liver fat beyond energy balance. As stated above, however, larger iso-caloric interventions are needed to confirm the present observations.…”
Section: Discussionsupporting
confidence: 92%
“…The MED diet score inversely associated with liver fat content and NAFLD in the present study. This result is in line with findings from other observational studies [34] and with experimental data to suggest protection from excess liver fat accumulation due to the high anti-oxidant contents of the MED diet [12,13]. Interestingly, in a recent cross-sectional study that reported an inverse association between adherence to the MED diet and NAFLD, the statistical effect was attenuated by adjusting for BMI [35], and iso-caloric dietary interventions trials are of special interest.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Environmental factors, especially dietary factors, also contribute to NAFLD development and progression [59,60]. The Western diet, which is particularly rich in added fructose, is associated with a greater risk of NAFLD, whereas the Mediterranean diet, which is high in polyunsaturated fatty acids (PUFAs), monounsaturated fatty acids (MUFAs), and fiber, has a beneficial effect on NAFLD [61,62]. Several nutrients impact the metabolic pathways leading to the lipid accumulation that characterizes the NAFLD initiation step, whereas others modulate key features in the pathogenesis of NASH, such as oxidative stress and inflammation.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…A reduced amount of total fats should constitute less than 30% of the total energy input, with a decrease in saturated fats and refined sugar intake and an increase in soluble fiber intake (low-fat diet). New evidence supports the idea that the Mediterranean (Med diet) may have an important role in the prevention and treatment of NAFLD [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 95%